PERSEPSI DAN MINAT MANAJEMEN CU TERHADAP PEMBANGUNAN BERKELANJUTAN DAN PELAPORAN BERKELANJUTAN - Kunradus Kampo (Fakultas Ekonomi dan Bisnis Universitas Atma Jaya Makassar, 2021)
This study aims to analyze the perceptions of Credit Union (CU) managers regarding sustainable development and interest in sustainable reporting. Respondents were asked to answer the questionnaire personally via google form. The SPSS output which became the focal point included descriptive statistical data, perception frequency and management interest. The results of the study indicate that CU management has a very good perception of sustainable development and sustainable reporting. In addition, CU management also has a high enough interest in implementing sustainable reporting. CU management has a good perception of the triple bottom line concept: profit, people, and planet and is interested in implementing sustainable reporting because it is an embodiment of CU's main value, namely love. The triple bottom line is strategically in line with CU's vision of economic, social and environmental vision and CU's management has implemented it in governance and activities through their work programs and annual budgets.